Sequencing and speed of reforms in an economic liberalization. programme : a comparative study. Emanuela di Gropello - Gropello, Emanuela di; International Development Centre, Centro Studi Luca d'Agliano (Italia) (Torino, Italia : International Development Centre, 1992)
Estudio comparativo de el paquete de reformas en los programas de liberación económica
Keywords: TEORIA ECONOMICA; CRECIMIENTO ECONOMICO; POLÍTICA FINANCIERA